2016
DOI: 10.1111/asj.12698
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mycoplasmal pneumonia of swine (MPS) lung lesion‐selected Landrace pigs on MPS resistance and immune competence in three‐way crossbred pigs

Abstract: To clarify the genetic influence of mycoplasmal pneumonia of swine (MPS) lesion-selected Landrace (La) on MPS resistance and immune characteristics in three-way crossbred pigs (LaWaDa), the LaWaDa pigs were compared with the non-selected crossbred (LbWbDb) and purebred (La) pigs. The MPS lesion score in the three lines was as follows: La line < LaWaDa line < LbWbDb line, with significant differences among the lines. The proportions of myeloid cells and T cells were lower and higher, respectively, in the LaWaDa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Previous reports by Katayama, Shimazu and Borjigin (Borjigin et al, 2016;Katayama et al, 2011;Shimazu et al, 2013Shimazu et al, , 2014 pigs. Borjigin also reported that the immune responses in MPSselected landrace pigs and other pig mix-breed lines were genetically distinct (Borjigin et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous reports by Katayama, Shimazu and Borjigin (Borjigin et al, 2016;Katayama et al, 2011;Shimazu et al, 2013Shimazu et al, , 2014 pigs. Borjigin also reported that the immune responses in MPSselected landrace pigs and other pig mix-breed lines were genetically distinct (Borjigin et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Previous reports by Katayama, Shimazu and Borjigin (Borjigin et al., 2016; Katayama et al., 2011; Shimazu et al., 2013, 2014) suggested that MPS‐selected landrace pigs had different immunological reactions, which depend on immunophenotype with experiments of injection of sheep red blood cells (SRBCs) or vaccination against M.hp, compared non‐treated pigs. Borjigin also reported that the immune responses in MPS‐selected landrace pigs and other pig mix‐breed lines were genetically distinct (Borjigin et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation